Relationship Between Motivation and Discipline of Students to Student Learning Outcomes Class XI Vocational High School - Astuti, Puji (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Abstract: Learning outcomes are used as benchmarks used to measure students' success in bsorbing lessons and as an evaluation material for teachers in delivering learning material. Student learning outcomes can be influenced by various factors including learning discipline factors and student motivation factors. The purpose of the study was to see how the students' motivation and discipline relate to the results of learning English class students XI of SMK Bina Bangsa Kayuagung OKI. The design of this study was quantitative descriptive with cross sectional. Data collection uses secondary data. Data analysis techniques were processed by chi-square test with a significant level of 95 and the largest error rate (?) of 0.05 or 5%. The results of the analysis of learning motivation towards students' learning outcomes in English were obtained ?-value 1,000 (> ? 0.05) and learning discipline towards students' English learning outcomes obtained ?-value 0.142 (> ? 0.05) it means that there is no meaningful relationship between motivation and learning discipline with the results of learning English in class XI SMK Bina Bangsa Kayuagung OKI. Students should improve and have curiosity and care about the acquisition of learning values. For schools to always provide opportunities and motivations for teachers to do more self-development which later can contribute positively to improving student learning outcomes.